Application of Problem-Based Learning in Banking Economics Courses to Improve Financial Analysis Skills - Marisya, Fitria (LIMEEMAS: Jurnal Ilmiah Pendidikan, 2026)
This study aims to analyze the effectiveness of Problem-Based Learning (PBL) in improving students' financial analysis skills in banking economics courses. The background of this research stems from students' limited ability to interpret financial data and solve banking cases analytically. The method used is a quantitative, quasi-experimental design of the one-group pretest-posttest type. The research subjects were 30 students from the financial management study program. The research instruments include financial analysis ability tests and observation sheets of learning activities. Data were analyzed using paired sample t-test and N-gain tests. The results showed a significant increase in pretest-to-posttest scores (p < 0.05), with an average N-gain of 0.58, which was in the medium range. In addition, observations revealed changes in student behavior, including increased participation, greater confidence, and improved ability to deliver analysis. These findings show that PBL is effective in improving students' financial analysis skills cognitively and practically. This research is expected to serve as a reference for the development of banking economics learning that is more contextual and grounded in real problems.